Reply to “Comment on «Stratigraphy of the Northern Pulo do Lobo Domain, SW Iberia Variscides: A palynological contribution» by Zélia Pereira et al. (2018) – Geobios 51, 491–506” - Pereira, Zélia (2020)
ABSTRACT: The main comments made by M.F. Pereira et al. to Pereira et al. (2018) relate to the discussion of the palynological age vs. U/Pb geochronological age based on detrital zircons, stating that “this discussion is inconsistent due to: (i) the impossibility that primary igneous ages in zircon grains would have been rejuvenated during Early Carboniferous low-grade regional metamorphism, and (ii) a wrong interpretation of the meaning and implications of maximal depositional ages derived from the youngest detrital zircon population”.